Personality correlates to performance under stress in simulated chemical plant emergencies. - Lehmann, Hans Peter. (2011)
When a fault develops in a chemical plant process, the plant operator must identify the fault rapidly and take immediate corrective action. The interaction of process factors varies from fairly to highly complex (in extreme cases, this interaction is not yet fully understood even by chemical engineers) and consequences of faults can occur in chainreactions. The operators task is to control all process parameters until the plant is brought back to normal conditions. Doing this, he is fully aware of the fact, that the consequences of wrong corrective action or failure to bring the plant under control can be grave in economic terms, extremely serious (lethal) in terms of the operator's hazards and potentially catastrophic. Thus a considerable amount of stress can be built up, which is potentially interfering with the "cool" required to succeed in overcoming the emergency as quickly and efficiently as possible. This project attempts to explore presumed correlations between personality factors and performance under stress. Where such correlations exist in significant manifestation, their rank of magnitude was established and their predictive value investigated. === Thesis (M.A.)-University of Natal, 1977.